Criminal Liabilty for Perpetrator Who Escaped During Covid-19 Quarantine: Case Study of Rachel Vennya - Sukmawati, Erika; Hidayat, Nur Azizah (Academos, 2022)
Can perpetrators who run away during the Covid-19 quarantine be subject to criminal liability and then What are the legal consequences for perpetrators who run away during the Covid-19 quarantine. The purpose of this article is to find out criminal liability and legal consequences for perpetrators who run away from the Covid-19 quarantine. The research methodology used in this research is normative legal research by statute approach to law is based on primary and secondary legal materials. This research resulted in an explanation of how criminal liability and legal consequences are for perpetrators who run away during the Covid-19 quarantine. From the results of the study, it can be seen that : a. Perpetrators of violations who escape from quarantine can be subject to criminal liability. b. Criminal sanctions for violating health quarantine are regulated in Article 93 of Law no. 6 of 2018 concerning Health Quarantine, which regulates parties who violate Article 9 paragraph (1) are threatened with a maximum imprisonment of one year and/or a maximum fine of Rp. 100 million.